Customer Retention Enhancement Strategies Using Bal-anced Scorecard During Service Expansion and Excellence Center Development - Riny Tri Yuliandita; M.Natsir Nugroho; Nofierni Nofierni (International Journal of Economics and Management Sciences, 2026)
The premium healthcare industry in urban areas is experiencing increasing competition along with the increase in healthcare facilities and the increasing public demand for fast, comfortable, and quality medical services. In this context, Columbia Asia Pulomas Hospital is implementing an expansion strategy by increasing facility capacity, modernizing services, and adding a Center of Excellence (COE) as a service differentiation. This study aims to analyze customer retention strategies within the Balanced Scorecard (BSC) framework, focusing on the relationship between customer perspectives, internal processes, learning and growth, and their application to the financial perspective. The research method uses a document-based policy and strategy analysis approach, field findings, and a synthesis of Balanced Scorecard theory and patient experience.The analysis shows that customer retention during the expansion phase is influenced not only by clinical quality, but also by the assurance of doctor time in practice, speed of service, physical comfort, and digitization of queues and administration. The addition of a COE has been shown to increase the perception of service value and expand market share through service specialist differentiation. Within the BSC framework, the customer perspective serves as a leading indicator for achieving the financial perspective, where increased patient retention contributes to increased revenue, ROI growth, and long-term financial expectations. The research implications emphasize that strategies for strengthening human resources, modernizing internal processes, and service innovation are important foundations in ensuring successful hospital expansion and enhancing competitive advantage.